Macrophage Migration Inhibitory Factor Inhibits the Antiinflammatory Effects of Glucocorticoids via Glucocorticoid‐Induced Leucine Zipper. Issue 8 (August 2014) - Fan, Huapeng; Kao, Wenping; Yang, Yuan H.; Gu, Ran; Harris, James; Fingerle‐Rowson, Günter; Bucala, Richard; Ngo, Devi; Beaulieu, Elaine; Morand, Eric F.
<x xml:space="preserve">Abstract</x> Objective Glucocorticoids remain a mainstay in the treatment of rheumatoid arthritis (RA). Dose‐dependent adverse effects highlight the need for therapies that regulate glucocorticoid sensitivity to enable dosage reduction. Macrophage migration inhibitory factor (MIF) is a proinflammatory protein that has been implicated in the pathogenesis of RA; it impairs glucocorticoid sensitivity via MAPK phosphatase 1 (MKP‐1) inhibition. The intracellular protein glucocorticoid‐induced leucine zipper (GILZ) mimics the effects of glucocorticoids in models of RA, but whether it represents a target for the modulation of glucocorticoid sensitivity remains unknown. We undertook this study to investigate whether GILZ is involved in the regulation of glucocorticoid sensitivity by MIF. Methods GILZ expression was studied in the presence and absence of MIF, and the role of GILZ in the MIF‐dependent regulation of the glucocorticoid sensitivity mediator MKP‐1 was studied at the level of expression and function. Results GILZ expression was significantly inhibited by endogenous MIF, both basally and during responses to glucocorticoid treatment. The effects of MIF on GILZ were dependent on the expression and Akt‐induced nuclear translocation of the transcription factor FoxO3A. GILZ was shown to regulate the expression of MKP‐1 and consequent MAPK phosphorylation and cytokine release. Conclusion MIF exerts its effects on MKP‐1 expression and MAPK activity through inhibitory effects on GILZ. These findings suggest a previously unsuspected interaction between MIF and GILZ and identify GILZ as a potential target for the therapeutic regulation of glucocorticoid sensitivity.